Perceptions, Challenges and Coping Strategies of Mathematics Teachers in the Implementation of Limited Face-To-Face Classes - Gumera, Meryl Fe; Ancog, Elmar B. (International Journal of Educational Innovation and Research, 2023)
This study investigated how mathematics teachers at Ozamiz City School of Arts and Trades perceived the implementation of limited face-to-face classes. The researcher purposively identified ten (10) secondary mathematics teachers, parents, and students who have participated in the implementation of limited face-to-face classes. A semi-structured interview was utilized to interview the Mathematics teachers, parents, and students at OCSAT. All online and offline interviews were recorded and verified because the researcher sought to capture the data precisely and comprehensively. Using Merriam Case Study Model, particularly a three-component triangulation, the outcome is supported by the feedback from parents and students to have an authenticity of results from the main respondents. This model helps identify the perceptions, challenges encountered, coping strategies, and suggestions and recommendations by the mathematics teachers in implementing limited face-to-face classes. Results showed that mathematics teachers acquire a sense of positivity because, with almost two (2) years of modular distance learning, teachers become excited to teach again. However, disadvantages occur using this modality that make teachers drained physically and mentally. With inconsistent findings using dissonance theory, the need to resume full in-person instruction was concluded.